TBAJ-876 retains bedaquiline’s activity against subunits c and ε of mycobacterium tuberculosis F-ATP synthase - Sarathy, Jickky Palmae (2020)
The antituberculosis drug bedaquiline (BDQ) inhibits Mycobacterium tuberculosis F-ATP synthase by interfering with two subunits. Drug binding to the c subunit stalls the rotation of the c ring, while binding to the ε subunit blocks coupling of c ring rotation to ATP synthesis at the catalytic α3:β3 headpiece. BDQ is used for the treatment of drug-resistant tuberculosis. However, the drug is highly lipophilic, displays a long terminal half-life, and has a cardiotoxicity liability by causing QT interval prolongation. Recent medicinal chemistry campaigns have resulted in the discovery of 3,5-dialkoxypyridine analogues of BDQ that are less lipophilic, have higher clearance, and display lower cardiotoxic potential. TBAJ-876, which is a new developmental compound of this series, shows attractive antitubercular activity and efficacy in a murine tuberculosis model. Here, we asked whether TBAJ-876 and selected analogues of the compound retain BDQ’s mechanism of action. Biochemical assays showed that TBAJ-876 is a potent inhibitor of mycobacterial F-ATP synthase. Selection of spontaneous TBAJ-876-resistant mutants identified missense mutations at BDQ’s binding site on the c subunit, suggesting that TBAJ-876 retains BDQ’s targeting of the c ring. Susceptibility testing against a strain overexpressing the ε subunit and a strain harboring an engineered mutation in BDQ’s ε subunit binding site suggest that TBAJ-876 retains BDQ’s activity on the ε subunit. Nuclear magnetic resonance (NMR) titration studies confirmed that TBAJ-876 binds to the ε subunit at BDQ’s binding site. We show that TBAJ-876 retains BDQ’s antimycobacterial mode of action. The developmental compound inhibits the mycobacterial F-ATP synthase via a dual-subunit mechanism of interfering with the functions of both the enzyme’s c and ε subunits.